Water - Baines, John (Wayland Hove, 1991)
"Water" by John D. Baines, published in 1993, is part of the "Links" series. This 32-page book emphasizes the critical importance of water as our most essential resource and explores the various ways it contributes to our daily lives. The content is enriched with color photographs and diagrams to aid understanding.